Chloro-s-triazines-toxicokinetic, Toxicodynamic, Human Exposure, and Regulatory Considerations - Abass, Khaled; Pelkonen, Olavi; Rautio, Arja (Current Drug Metabolism, 2021)
Chloro-s-triazines-atrazine, cyanazine, propazine, simazine, and terbuthylazine-are structurally similar herbicides, differing only in specific s-triazine4-and 6-N alkyl substituents. It is generally regarded that their toxicokinetics, such as, metabolic pathways, biological effects and toxicities, also share more similar features than the differences. Consequently, it is useful to compare their characteristics to potentially find useful structure-activity relationships or other similarities or differences regarding different active compounds, their metabolites, and biological effects including toxic outcomes. The ultimate goal of these exercises is to apply the summarized knowledge-as far as it is possible regarding a patchy and often inadequate database-to cross the in vitro-in vivo and animal-human borders and integrate the available data to enhance toxicological risk assessment for the benefit of humans and ecosystems.
Keywords: regulatory guidance